2011
DOI: 10.4236/msa.2011.25043
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activated Carbon Monoliths for Methane Adsorption Obtained from Coffee Husks

Abstract: Methane adsorption by different forms of activated carbon obtained from coffee husks, including monolith honeycomb and disc types, was studied by activation with zinc salts and potassium hydroxide at 298.15 K and 303.15 K and pressures up to 30.00 atm in a volumetric adsorption apparatus. We observed increased methane adsorption capacity on a mass basis in the different activated carbon monoliths with increasing surface area, total pore volume and micropore volume, with the honeycomb type displaying the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…To overcome this problem, the powders can be pelletized or granulized to obtain a larger particle size [ 112 ]. Another possible solution is to shape the activated carbons into honeycombs or other types of monoliths [ 112 , 113 , 114 ].…”
Section: Characterization Of Activated Carbonsmentioning
confidence: 99%
“…To overcome this problem, the powders can be pelletized or granulized to obtain a larger particle size [ 112 ]. Another possible solution is to shape the activated carbons into honeycombs or other types of monoliths [ 112 , 113 , 114 ].…”
Section: Characterization Of Activated Carbonsmentioning
confidence: 99%
“…Adsorbents require both large pore volume and high specific surface area [ 34 ]; however, it is not easy to obtain a sintered product with a high specific surface area. The results of this study showed that plastic carbide residue increases the specific surface area of ceramics, so it would be of great significance if a method for increasing the specific surface area of sintered products was established.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, methane adsorption was investigated on activated carbon obtained from coffee husks [29] at 298.15 K and 303.15 K and pressures up to 30.00 atm. maximum volumetric methane uptake by the synthesised carbon monoliths was observed to be 130 V/V at 298.15 K and 30.00 atm.…”
Section: Adsorption Of Ch 4 and Co 2 Mixturementioning
confidence: 99%